Indicators of sustainable rehabilitation of hospital buildings (Journal of Architectural Design, 2023)
The organizing principle of sustainability concepts in the built environment have often been seen as the principles of sustainable development or development that meet the needs of the present without compromising the ability of future generations to meet their own needs. Preserving buildings is an important factor in sustainability indicators because it achieves the economic, cultural, social, and environmental principles associated with sustainable development paths, as building rehabilitation is one of the means of preserving it. In addition to the exacerbation of global environmental problems, especially the problems of contemporary climate change, the energy crisis, as well as the lack of material resources, which negatively affected healthcare facilities .The research problem was represented by, "insufficient knowledge that explains the indicators of rehabilitation of existing hospital buildings by the principles of sustainable architecture." From this standpoint, hospital buildings became a central focus of international discussions, necessitating the transition to a sustainable healthcare system, and for most of the existing health buildings. The research dealt with the importance of sustainable rehabilitation of the reality of existing hospital buildings, to keep pace with contemporary medical developments, and new and innovative technologies for most of its nursing, diagnostic, and therapeutic departments, through the principles of sustainability, and for the general urban environment of its basic components and environmental surroundings. The research methodology represented the descriptive analytical approach of the most important elements of rehabilitation and its levels according to the foundations of sustainability (environmental, social, and economic) of the architectural structure system of hospital buildings and how it was applied to international experiences of hospitals